Prevalence and causes of blindness among Macedonian population - Dimitrova Radojichikj, Daniela (My University, 2017)
Goal: To determine prevalence and causes of blindness among adults (> 26 years age) in five municipalities in the Republic of Macedonia. Methods: The ophthalmology statements of registered people with blindness who are beneficiaries of social welfare in 2015 were reviewed. Results: A total of 475 records were included in the research. The mean age of the persons was 64.1 (range 26-87), both male and female. Blindness was found to be significantly associated with increasing age (p<0.001). There was gender difference in the prevalence of blindness (p=0.0310). The rate of blindness was estimated to be 0.24% (95% CI:0.22-0.26). The most common causes were cataract (23.2%), then glaucoma (21.7%) and diabetic retinopathy (12.8%). Many of the causes of blindness were potentially avoidable, with cataract and glaucoma as leading etiology. Conclusion: The results of this study point to the initiation of coordinated activities to prevent blindness caused from cataract, glaucoma, and diabetic retinopathy.
Keywords: prevalence, age, gender, causes of blindness